2011
DOI: 10.1593/tlo.11256
|View full text |Cite
|
Sign up to set email alerts
|

Glut-1 Expression Correlates with Basal-like Breast Cancer

Abstract: Our results show that Glut-1 is significantly associated with BLBC and might be a potential therapeutic target for this aggressive subgroup of breast cancer, and this warrants further investigations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
69
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(70 citation statements)
references
References 39 publications
1
69
0
Order By: Relevance
“…Likewise, as GDH activity is influenced by various factors, it is presumed that GDH activity is not directly proportional to glutamine uptake by ASCT2 or GLS activity. Furthermore, basal-like type and/or TNBC has been shown to exhibit the highest glycolysis-related protein activity, including Glut1 (SLC2A1) and CAIX (CA9) (Hussein et al 2011, Pinheiro et al 2011. Taken together, the low level of GDH activity observed in TNBC in this study can be explained by its high level of glycolytic activity.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Likewise, as GDH activity is influenced by various factors, it is presumed that GDH activity is not directly proportional to glutamine uptake by ASCT2 or GLS activity. Furthermore, basal-like type and/or TNBC has been shown to exhibit the highest glycolysis-related protein activity, including Glut1 (SLC2A1) and CAIX (CA9) (Hussein et al 2011, Pinheiro et al 2011. Taken together, the low level of GDH activity observed in TNBC in this study can be explained by its high level of glycolytic activity.…”
Section: Discussionmentioning
confidence: 49%
“…Therefore, metabolic status is also expected to differ according to molecular subtype. Previous studies support this expectation, having identified aerobic glycolysisrelated proteins such as GLUT1 (SLC2A1) and CAIX (CA9), which are highly expressed in basal-like type and/or triple-negative breast cancer (TNBC; Hussein et al 2011, Pinheiro et al 2011). However, relatively few studies have considered differences in glutamine metabolism according to the molecular subtypes of breast cancer.…”
Section: Introductionmentioning
confidence: 82%
“…3 Previous studies indicated that upregulation of GLUT-1 contributed to an improved glucose metabolism, which was required in proliferating cancer cells. 2 GLUT-1 is overexpressed in many tumors, including breast, 4 colorectal, 5 endometrial, 6 and ovarian 7 carcinomas. GLUT-1 was reported originally as a marker of infantile skin hemangioma.…”
Section: Introductionmentioning
confidence: 99%
“…Compounds possessing peptide mimic as transporter recognition unit can be transported into cancer cells by PEPT1. GluT1 (glucose transporter 1) is overexpressed in cancer cells, particularly in breast cancer cells compared to healthy breast cells [11,12]. Incorporating glucose mimic as transporter recognition unit into novel compounds may develop cell-permeable anti-cancer drugs due to the glucose transport system.…”
Section: Specific Overexpression Of Slc Transporters In Cancer Cellsmentioning
confidence: 99%